Public governance as co-creation a strategy for revitalizing the public sector and rejuvenating democracy - Ansell, Christopher K. 1957-; Torfing, Jacob 1963- (Cambridge studies in comparative public policy, 2021)
We need new governance solutions to help us improve public policies and services, solve complex societal problems, strengthen social communities and reinvigorate democracy. By changing how government engages with citizens and stakeholders, co-creation provides an attractive and feasible approach to governance that goes beyond the triptych of public bureaucracy, private markets and self-organized communities. Inspired by the successful use of co-creation for product and service design, this book outlines a broad vision of co-creation as a strategy of public governance. Through the construction of platforms and arenas to facilitate co-creation, this strategy can empower local communities, enhance broad-based participation, mobilize societal resources and spur public innovation while building ownership for bold solutions to pressing problems and challenges. The book details how to use co-creation to achieve goals. This exciting and innovative study combines theoretical argument with illustrative empirical examples, visionary thinking and practical recommendations